A study on factors influencing customer complaint behaviour / Hani Yusrina Yahaya and Siti Afiqah Nasruddin - Yahaya, Hani Yusrina; Nasruddin, Siti Afiqah (2018)
The knowledge and understanding of quality standards of guests helps the hotel improve the quality of hotel services and increase guest satisfaction with the hotel stay. In every hotel provide their own procedures and policies that may lead the guest had a different of an experience. There exist a large number of factors that influence guest impressions from the sector of product and services they provided. Besides, the organization has to be aware of the strengths and weaknesses of their business and the operation of the hotel management to identify the improvements and innovations which could bring additional value towards the guest. By proving improvements towards the organization may enhance the profits plus, could reach the goal of the organizations.